Abundance and survival estimates of the southeastern Pacific humpback whale stock from 1991–2006 photo-identification surveys in Ecuador - Félix, Fernando; Castro, Cristina; Laake, Jeffrey L. (The journal of cetacean research and management, 2020)
Southeastern Pacific humpback whales (Breeding Stock G) breed along the northwestern coast of South America and farther north up to CostaRica. Photo-identification surveys conducted aboard whalewatching vessels during the migration/breeding season from June to September between1991 and 2006 off the coast of Ecuador (2°S, 81°W) have produced a database of 1,511 individual whales. Comparisons of photographs produced190 between-year re-sightings of 155 individual whales. Closed and open capture-recapture models were used to estimate abundance and survival.The best estimate of abundance in 2006 with the Chapman modified-Petersen was 6,504 (95% CI: 4,270–9,907; CV = 0.21). Abundance estimatesfrom open population models were considerably lower due to heterogeneity in capture probability which produced a ‘transient’ effect. Our bestestimate of true survival was 0.919 (95% CI: 0.850–0.958). Heterogeneity most likely occurred from inter-annual variation in sampling and unknownstructure and variation in the migration timing and corridor. A more extensive collaborative effort including other wintering areas further north aswell as integrating breeding-feeding data will help to reduce heterogeneity and increase precision in abundance and survival estimates.